Climate responsive strategies of traditional dwellings located in an ancient village in hot summer and cold winter region of China. (April 2015) - Gou, Shaoqing; Li, Zhengrong; Zhao, Qun; Nik, Vahid M.; Scartezzini, Jean-Louis
Abstract: Global warming and energy shortage have aroused a great interest in climate responsive strategies of vernacular dwellings during recent years. This study focuses on a qualitative analysis of ancient dwellings located in the village of Xinye, in the hot summer and cold winter region of China. Furthermore, a typical ancient dwelling located in the village was selected for assessment of its indoor thermal environment on the basis of an on-site monitoring, carried out in summer and winter. Whole annual thermal performance of the dwelling was also investigated using EnergyPlus simulations. The field measurements were used to outline the effectiveness of the climate responsive strategies. According to the analysis, the climate responsive strategies of the dwellings are mainly focused on natural ventilation, sun shading and thermal insulation, illustrated by different building aspects such as the building location, building group layout and orientation, internal space arrangement, opening design and among other variables. Thermal simulations reveal that the traditional dwelling located in Xinye village is well adapted to the local climate during summertime, although the indoor thermal comfort is not fully satisfactory during wintertime. Highlights: Climate responsive strategies of Chinese traditional dwellings are illustrated. Indoor thermal environment of a typical dwelling is assessed by on-site monitoring. Annual thermal performance of the dwelling is evaluated by EnergyPlus simulation. The Chinese traditional dwelling is well adapted to the local climate in summertime. Ancient construction wisdoms can provide low energy solutions for the modern world.